THE EXPECTATION AND THE ACTUAL CONDITION OF CONSUMERS TOWARD PARCEL DELIVERY SERVICE IN HAT YAI DISTRICT, SONGKHLA PROVINCE - Petcharat, Suwatchanee; Plongoon, Kanjana; Srldam, Sirlkan; Methanai, Chakkiat Methanai; Rorbkorb, Narongsak (Journal of Buddhist Anthropology, 2022)
The objectives of this research were 1) to study the expectation and the realistic conditions of the consumer's parcel delivery service, 2) to compare the expectation and the realistic conditions of the consumer's parcel delivery service, and 3) to compare the expectation and realistic conditions toward parcel delivery services according to the age of the consumer. The samples were 400 consumers in Hat Yai district, Songkhla province who had experienced parcel delivery service and this research use simple random sampling. The statistics used were mean, standard deviation, t-test, F-test and pairwise comparison. The results were as follows: 1) The overall expectation of the parcel transportation service was at a high level and when considering each aspect It was found that all aspects were at a high level. As for the actual condition of the parcel delivery service, it was found that the overall level was at a high level and when considering each aspect, it was found that all aspects were at a high level, too. 2) The comparison of expectation and realistic conditions was found that the overall was not significantly different at the .05 level. When considering each aspect, it was found that price, distribution channel, personnel, service process and the presentation of physical characteristics were significant difference at the .05 level. 3) The comparison of expectation and realistic conditions toward parcel delivery services by age found people different ages had expectation of parcel delivery services differs significantly at the .05 level and for realistic conditions significantly different at the .01